AGN feedback and the origin of the α enhancement in early-type galaxies – insights from the GAEA model. (5th December 2016) - De Lucia, Gabriella; Fontanot, Fabio; Hirschmann, Michaela
Abstract: We take advantage of our recently published model for GAlaxy Evolution and Assembly (GAEA) to study the origin of the observed correlation between [α/Fe] and galaxy stellar mass. In particular, we analyse the role of radio-mode active galactic nuclei (AGN) feedback, which recent work has identified as a crucial ingredient to reproduce observations. In GAEA, this process introduces the observed trend of star formation histories extending over shorter time-scales for more massive galaxies, but does not provide a sufficient condition to reproduce the observed α enhancements of massive galaxies. In the framework of our model, this is possible only by assuming that any residual star formation is truncated for galaxies more massive than 10 10.5  M⊙ . This results, however, in even shorter star formation time-scales for the most massive galaxies, which translate in total stellar metallicities significantly lower than observed. Our results demonstrate that (i) trends of [α/Fe] ratios cannot be simply converted into relative time-scale indicators; and (ii) AGN feedback cannot explain alone the positive correlation between [α/Fe] and galaxy mass/velocity dispersion. Reproducing simultaneously the mass–metallicity relation and the α enhancements observed pose a challenge for hierarchical models, unless more exotic solutions are adopted such as metal-rich winds or a variable initial mass function.